Cytokeratin 5 and cytokeratin 20 inversely correlate with tumour grading in Ta non‐muscle‐invasive bladder cancer. Issue 16 (29th June 2021) - Muilwijk, Tim; Akand, Murat; Van der Aa, Frank; De Coninck, Vincent; Claessens, Marc; Hente, Robert; Eckstein, Markus; Allory, Yves; Libbrecht, Louis; Joniau, Steven; Gevaert, Thomas
Abstract: Cytokeratin 5 is a marker of basal molecular subtypes of muscle‐invasive bladder cancer (MIBC), which correlates with worse overall survival compared to luminal subtypes. Our observations have not confirmed CK5 as a marker of high‐grade (HG) disease in Ta non‐muscle‐invasive bladder cancer (NMIBC). Therefore, to understand the basal‐luminal immunohistochemistry profile in Ta NMIBC, we performed immunohistochemistry for CK5, P40, P63 (basal), GATA3 and CK20 (luminal) and studied the correlation with HG and clinical outcome in 109 patients with Ta NMIBC. HG and low‐grade (LG) diseases were scored in each patient. Four different CK5 patterns were evaluated: absent (median 41.3%), normal (72.5%), rising (84.4%) and full thickness (23.9%). The median percentage of GATA3 was 100%. HG disease and CK5 expression and rising CK5 pattern had a significant inverse correlation, whereas HG disease and CK20 expression had a significant positive correlation. We also found a significant inverse correlation between CK5 expression and CK20 expression. Quantitative PCR confirmed that the presence of CK5 correlated with up‐regulation of CK5 RNA. None of the markers could differentiate patients with regard to clinical outcome. Our results suggest a role for CK5 and CK20 in differentiating between LG and HG disease in Ta NMIBC.